2021
DOI: 10.1166/jmihi.2021.3371
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Brain Image Characteristics of Patients with Parkinson's Disease Under Multimodal Magnetic Resonance Technology

Abstract: In order to improve the early diagnosis rate of Parkinson's disease (PD), reduce the complications of PD in the later stage, and make the clinical intervention to alleviate the pain of Parkinson's patients early, Magnetic resonance imaging (MRI), positron emission tomography (PET), and computerized tomography (CT) were used to evaluate the characteristics of PD. A total of 34 patients diagnosed with PD admitted to Qilu Hospital of Shandong University from January 2017 to December 2018 were included in the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[32] The authors suggested that at least one other cognitive process (acoustic tone duration processing) accounted for the speech perceptual deficit in people with PD. [33] A study about magnetic resonance imaging in patients with hypokinetic dysarthria from Liu [34] found that the subcortical gray matter volume in the hippocampus of these patients is significantly reduced. In addition, Li et al [35] also found that the brain electrical activity of cognition-related regions such as inferior frontal gyrus and prefrontal lobe increased significantly in patients with hypokinetic dysarthria.…”
Section: Cognitive Function Impairmentmentioning
confidence: 99%
“…[32] The authors suggested that at least one other cognitive process (acoustic tone duration processing) accounted for the speech perceptual deficit in people with PD. [33] A study about magnetic resonance imaging in patients with hypokinetic dysarthria from Liu [34] found that the subcortical gray matter volume in the hippocampus of these patients is significantly reduced. In addition, Li et al [35] also found that the brain electrical activity of cognition-related regions such as inferior frontal gyrus and prefrontal lobe increased significantly in patients with hypokinetic dysarthria.…”
Section: Cognitive Function Impairmentmentioning
confidence: 99%